Living on the land: indigenous women's understanding of place - Altamirano-Jiménez, Isabel; Kermoal, Nathalie J.; Horn-Miller, Kahente (AU Press, 2016)
From a variety of methodological perspectives, contributors to Living on the Land explore the nature and scope of Indigenous women's knowledge, its rootedness in relationships, both human and spiritual, and its inseparability from land and landscape.
Le texte de Horn Miller, Kahente (2016). Distortion and Healing: Finding Balance and a ‘Good Mind’ through the rearticulation of Sky Woman’s Journey, a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; canada; cours; cree; discipline; environnement; féminisme autochtone; histoire; métis; naskapi; nicaragua; pol4105; premier cycle; ressource en ligne; régions géographiques; sciences humaines; thématiques; études autochtones; île de la tortue